Rancang Bangun Sistem Informasi Tempat Pemakamam Umum Pondok Rajeg Bogor Berbasis Web - Ibnu Rusdi; Indra Febria Widy; Hisyam Husein (Universitas Bina Sarana Informatika, 2019)
The use of information technology has a very broad scope. One of them is in the field of funeral. Funeral is often a